“Consumo de la información de la red social Facebook para lograr el posicionamiento de la imagen del Municipio del cantón Mejía” - Jácome Naranjo, Jean Carlo (2020)
The communication development in the digital age, represents a great contribution in a person position in an enterprise or institution, due to the new web platforms and specifically to Facebook app that works like a social media of information sharing. The government communication has gained dynamism, for that reason, this researching project has the objective to analyze the information consumption of social network Facebook in the web site of “Gobierno Autónomo Descentralizado (GAD) " in Mejia Canton. In this research I used a nonexperimental design, transverse, and descriptive sort, and It was applied a quantitative and qualitative analysis to define the amount of information, the use of the social website Facebook like a position and informative tool identifies the kind of users that needs the information and propose a matrix of strategic communications, the information was obtained from a pattern of 400 people that live in Machachi, through the implementation of a survey with 14 closed questions, focused on getting the enough information to achieve the goals of this research. This survey was developed online through Facebook, using different allowed technological tools. In order to get the results, statist’s tools were applied, by keeping on mind the percentage values to tabulate the obtained data. After checking the utility of Facebook as a tool of communication from Mejia municipality, we determined like positive, because around 87.9% users use up Facebook as mean of communication. The cybernetic ally active users that follows Facebook website in Mejia GAD are young and adult people between 20 to 31 years’ old which prefer this social media cause of the advantages. Furthermore, we identified that the information has to be published on time, has to be varied, in full and weekly way, referring to the projects, the same ones with an easy manage through audiovisuals, photos, text, videos among others. By x easing the information rights to the population through this digital tool and allowing the dynamic information, interactive and winsome. Finally, that the comments received in this digital platform are not considered, laying off, the feedback in this communicative too